Developing Asthma-Friendly Childcare Centers with Online Training and Evaluation - Alexandra Catherine Hayes Nowakowski; Henry Joseph Carretta; Nicole ePineda; Julie Kurlfink Dudley; Jamie R Forrest (Frontiers Media S.A., 2016)
In 2011, the Florida Asthma Coalition began offering its Asthma-Friendly Childcare Center training online. This course teaches childcare center employees the fundamentals of effective asthma management. It covers basic asthma physiology, ways to recognize asthma attacks, techniques to help children experiencing attacks, and strategies to create healthy environments for asthmatics. A team of health services researchers evaluated both years of the online training. Evaluators used a quasi-experimental design with pretest, posttest, and follow-up assessment. Questions measured knowledge gain and retention, user satisfaction, and implementation of management strategies. Over 650 people from nearly all 67 Florida counties took AFCC training online between 2011 and 2013. Test scores improved by a minimum of 11 percentage points in all program years evaluated. Gains in both knowledge and confidence were substantial and highly significant across years. While individual trainees did forget some content on follow-up, they seemed to retain the specific messages most relevant for their own workplaces. Most trainees also planned to implement multiple management strategies recommended by the training.A large majority of participants rated the training as excellent on all quality metrics, including relevance of content and time efficiency of the online format. Nearly all respondents perceived the training as useful for both providing improved care and fulfilling licensure or certification requirements. Many participants also indicated that their centers would pursue formal certification as AFCCs via the program offered by FAC. The online AFCC course performed strongly in its first years, yielding both high participant satisfaction and substantial improvement in workplace asthma management activity. This training holds promise for introducing and improving multidimensional asthma management strategies at childcare facilities nationwide.